Effect of swine residue rates on corn, common bean, soybean and wheat yield - Laércio Ricardo Sartor (Revista Brasileira de Ciência do Solo, 2012)
Swine residue (SR) applied as nutrient source of crops such as corn, bean, soybean and wheat, besides representing an environmental-friendly way of disposing of organic waste resulting from swine production, may significantly increase grain yields, replacing mineral fertilizer. The objective was to evaluate the effect of SR rates on corn, common bean, soybean and wheat yields from 2002 to 2007, in comparison with mineral fertilizer. The experiment was carried out at the Instituto Agronômico do Paraná - IAPAR, Pato Branco, PR and consisted of increasing SR rates (0, 15, 30, 45, and 60 m³ ha-1) and one treatment with mineral fertilizer (NPK 4-30-10), using 250 kg ha-1 for bean and 300 kg ha-1 for corn, soybean and wheat. Also, in the treatment with mineral fertilizer, 60, 120 and 90 kg ha-1 N was applied as topdressing to bean, corn and wheat, respectively. There were significant increases of grain yield in all evaluated years and crops with increasing SR rates, especially in the grass species under study. Also, with increasing SR rates applied every six months, K, P, Ca and Mg were accumulated in the soil and the pH increased. The application of 60 m³ ha-1 SR increased yields and exceeded the yield obtained with the recommended mineral fertilizer, indicating this amount as adequate for these crops.